IMPACT OF CONSTRUCTION AND RECLAMATION ACTIVITIES ON THE WATER QUALITY OF THE THANE CREEK, CENTRAL-WEST COAST OF INDIA - Goldin Quadros; Vidya Mishra; Mangal U. Borkar; R.P. Athalye (JOURNAL OF COASTAL DEVELOPMENT, 2004)
Degradation of natural resources is a major environmental issue the world is currently facing. Estuaries, creeks and coastal water ecosystems are such natural resources that are important as breeding and feeding grounds for fishes and crustaceans. Human activities and alterations made by reclamation have had an adverse effect on their ecology. Due to this, water quality management in these ecosystems has become a necessity. Regular studies of the hydrological parameters are essential for this purpose, as they can assess the status of pollution and help in deciding the mitigation strategy. Water quality of 26 km stretch of Thane creek, central-west coast of India was analyzed in 5 regions of the creek from May 1999 to April 2000. The study revealed spatial and temporal patterns. Heavy suspended solid load (avg. 5.736 gm/L), frequent hypoxia (DO<2.5 mg/L) coupled with excess nutrients like Phosphate-Phosphorus (avg. 0.26 mg/L) and Nitrate-Nitrogen (avg. 0.96 mg/L) were the main features of the creek. The Thane city region showed more deterioration of water quality compared to the other regions in the creek. In this region the suspended solid load showed an increase of 713.69% and dissolved oxygen decreased by 21.55% compared to the data of 1992-93. This can be attributed to the severe onslaught of activities in this region like solid waste dumping, construction of 3 new bridges, etc. since 1993, thereby affecting the flushing characteristic. Hence in order to protect and preserve such ecosystems, alterations to the environment should be meticulously planned.